Transformasi Pembelajaran Bahasa Indonesia melalui Kurikulum Merdeka dalam Menjawab Tantangan Literasi Generasi Digital - Hasib Hasib; Moh. Sugeng; Mahin Ainun Naim (Lembaga Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Keguruan dan Ilmu Pendidikan PGRI Sampang, Indonesia, 2026)
The formal education system in Indonesia is organized through schools and comprises various components, including foundational principles, objectives, curriculum, and evaluation. Evaluation is conducted to improve the educational process. This study aims to enhance the quality of the student learning process in the Indonesian Language subject at SMP Al-Ismailiyah Beringin, Tambelangan, Sampang. A qualitative approach was employed, with Grade VII students at SMP Al-Ismailiyah Tambelangan, Sampang, serving as the research subjects. Data collection techniques included observation, in-depth interviews, and documentation. Data analysis involved four stages: (1) data reduction, (2) data presentation, (3) verification, and (4) drawing conclusions. The study's findings indicate that: (1) Grade VII teachers at SMP Al-Ismailiyah plan instruction by creating teaching modules and preparing the Learning Objective Flow (ATP), Learning Objectives (TP), and Learning Outcomes (CP) to be achieved by students; they also undertake steps such as determining learning strategies and methods, preparing instructional media, designing